2020
DOI: 10.1183/23120541.00356-2019
|View full text |Cite
|
Sign up to set email alerts
|

Measures of lung function and their relationship with advanced glycation end-products

Abstract: BackgroundAdvanced glycation end-products (AGEs) have been implicated in the pathophysiology of chronic obstructive pulmonary disease (COPD). However, the association between AGE accumulation in the skin measured by skin autofluorescence (SAF) and lung function in healthy subjects has not been explored in detail. We use a population-based study of 50–64-year-olds to assess spirometry, diffusing capacity of the lung for carbon monoxide (DLCO) and impulse oscillometry (IOS) in relation to SAF.MethodsParticipants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…However, 17.1% of participants were current smokers in this study, which is comparable to the smoking prevalence in Sweden [45]. Lastly, the participants in this study were mainly Caucasian descent; the conclusions may not be generalizable to non-European ethnicities.…”
Section: Discussioncontrasting
confidence: 63%
“…However, 17.1% of participants were current smokers in this study, which is comparable to the smoking prevalence in Sweden [45]. Lastly, the participants in this study were mainly Caucasian descent; the conclusions may not be generalizable to non-European ethnicities.…”
Section: Discussioncontrasting
confidence: 63%
“…Although the precise mechanisms remain incompletely understood, there is also evidence suggesting that skin autofluorescence mirrors systemic nonenzymatic glycation processes. Our prior research has demonstrated a notable correlation between heightened AGE accumulation, quantified through skin autofluorescence, and discernible declines in lung function, signifying alterations in the lung parenchyma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke accelerates skin ageing and contains glycotoxins that induce AGE formation [24]. Enhanced SAF has indeed been shown in smokers compared to nonsmokers [25,26], as did the study by ZAIGHAM et al [7]. Some studies particularly measured SAF in the non-dominant arm to limit external effects of smoking.…”
mentioning
confidence: 86%
“…In the search for (noninvasive) biomarkers for COPD, studies have shown increased SAF in COPD as well, which inversely correlated with indices of lung function. In the current issue of ERJ Open Research , the study by Z aigham et al [ 7 ] is only the second to extend these findings into a population-based study, of mostly 50–64-year-olds.…”
mentioning
confidence: 99%
See 1 more Smart Citation